Patterns and Obstacles of Provision of Minor Orthopedic Procedures among Primary Care Physicians in Saudi Arabia - Al-Ahaideb, Abdulaziz; Khoshhal, Khalid; Alsiddiky, Abdulmonem; Heissam, Khaled; Alzakari, Abdulmajeed; Alsaleh, Khalid (International Journal of Health Sciences, 2012)
Introduction: Musculoskeletal disorders are common reasons for consultation with the primary care provider (PCP). For many of these disorders, treatment with minor procedures can bring about rapid and effective response with a very low complication rate. In reality, not many of these procedures are carried out in the primary care facilities in Saudi Arabia and in many other countries around. Materials and Methods: A cross sectional study design was chosen. The questionnaire aimed to quantify the number and different types of injections performed by PCPs; to evaluate the level of training and to identify barriers to PCPs performing joint and soft tissue injections in the primary care facilities. This questionnaire was distributed on 298 physicians working in primary care setting in Riyadh. The absolute frequency and percentages were calculated, and Chi square and ANOVA analyses were calculated and correlation test was done to procedures obstacles and their patterns. Results: One hundred and thirty physicians (43.6%) of the respondents have taken orthopedic training during their residency program. Among the respondents who have taken a training period during their residency 115 (88.5%) had orthopedic training for 4 weeks. Only 69 (53.1%) of them -who had training- had performed joint and soft tissue injections during their family medicine residency program. The top reasons cited for not performing the procedures were "Lack of up to date skills" and "limited consultation timeâ€ because of work overload. Conclusion: Many physicians working in primary care settings in Saudi Arabia refer patients requiring minor office procedures for specialist consultation. Treating patients at the primary care level can be more time and cost effective. These results uncover that there is a big need for improvement in orthopedic and rheumatology training during undergraduate medical vocational training and family medicine residency program. Key words: Minor orthopedic procedures, joint and soft tissue injection, Family medicine program, Primary care physician, Training program.